Full Utilization of Squid Meat and Its Processing By-products: Revisit. Issue 4 (19th May 2022) - Singh, Avtar; Mittal, Ajay; Benjakul, Soottawat
ABSTRACT: Squid mantle, tentacle, ovary, ink and visceral organs have been used as food or food ingredients. Mantle is consumed as raw, boiled and other forms such as surimi, dried-seasoned squid. Skin is used for the preparation of collagen or gelatin or their derivatives. Melanin-free ink, serine protease inhibitors from squid ovary and chitooligosaccharide from squid pen can be employed to improve the gel properties of dark and white fleshed surimi. This review provides the insight of full updated information on squid products and value-added products from squid discards. Their potential applications in food or related industries are also revisited.